The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1093/ndt/13.4.911
|View full text |Cite
|
Sign up to set email alerts
|

Radiocontrast-induced DNA fragmentation of renal tubular cells in vitro: role of hypertonicity

Abstract: The DNA fragmentation of MDCK cells induced by diatrizoate is related to its hypertonicity in this in vitro model of radiocontrast cytotoxicity. Nuclear disintegration with subsequent cell death may contribute to the pathophysiology of radiocontrast-induced nephropathy, particularly in the hypertonic/hypoxic environment of the renal medulla. The present results underscore the importance of avoiding hyperosmolal urine states in patients at high risk of radiocontrast-induced nephropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
1
4

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(52 citation statements)
references
References 2 publications
2
45
1
4
Order By: Relevance
“…[11][12][13][14] The direct toxic effects of CM have been studied in various cells, including renal epithelial and mesangial cells. 15 The functional and structural changes observed as a result of CM action included cell death, a decrease in cell viability, and an increase in brush border and lysosomal enzyme activity; 16 cellular DNA fragmentation; 17 downregulation of signaling molecules involved in cell survival such as Akt and upregulation of signaling molecules in cell death such as the p38 and c-Jun N-terminal kinase members of the mitogenactivated protein kinases and the transcription factor nuclear factor kB as well as caspase activation. 13,18,19 Nuclear factor kB and c-Jun N-terminal kinases are believed to be involved in the upregulation of the proinflammatory cytokine interleukin-8 (IL-8).…”
Section: Pathophysiology Of Ci-akimentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13][14] The direct toxic effects of CM have been studied in various cells, including renal epithelial and mesangial cells. 15 The functional and structural changes observed as a result of CM action included cell death, a decrease in cell viability, and an increase in brush border and lysosomal enzyme activity; 16 cellular DNA fragmentation; 17 downregulation of signaling molecules involved in cell survival such as Akt and upregulation of signaling molecules in cell death such as the p38 and c-Jun N-terminal kinase members of the mitogenactivated protein kinases and the transcription factor nuclear factor kB as well as caspase activation. 13,18,19 Nuclear factor kB and c-Jun N-terminal kinases are believed to be involved in the upregulation of the proinflammatory cytokine interleukin-8 (IL-8).…”
Section: Pathophysiology Of Ci-akimentioning
confidence: 99%
“…Cell cycle arrest may result as a consequence of cellular damage, in particular DNA damage, thus preventing the cell from entering cell division. Cellular DNA damage by CM has been reported; 17 and therefore, it is feasible that the CM may upregulate these cell cycle arrest markers in renal tubule cells and may be detected in urine after CM-induced renal injury.…”
Section: Cell Cycle Arrest Markersmentioning
confidence: 99%
“…In addition, in an in vitro model with a renal epithelial cell line, DNA fragmentation (a marker of apoptosis) was increased in cells exposed to hyperosmolar contrast media, and the degree of fragmentation was proportional to the osmolality of the contrast medium. 36 Thus, there is evidence of a direct cytotoxic effect of contrast media that is independent of hypoxia and may be related to hyperosmolality of the contrast agent. However, when the renal effects of isoosmolar contrast media, which have the lowest osmolality, were compared with the effects of hypo-and hyperosmolar contrast agents, there was no reduction in renal abnormalities with the iso-osmolar agents.…”
Section: Effect Of Osmolalitymentioning
confidence: 99%
“…Radiocontrast results in apoptosis of tubular epithelial cells in vivo (54) and in cultured cells (47,55). Hizoh et al (47) found that contrast-induced apoptosis in cultured cells was due to hyperosmolarity and not hypoxia. In contrast, other studies have found that epithelial cell apoptosis occurs after contrast-induced decreases in medullary oxygenation (54).…”
Section: Direct Tubular Toxicitymentioning
confidence: 99%